Dinámicas temporales en casos de feminicidio: ¿Qué papel juega el paso del tiempo como factor de riesgo? = Temporaldynamics in cases of femicide : what role does the passage of time play as a risk factor? - Hermoso, Jorge Santos (Behavior & Law Journal, 2022)
The filing of a complaint or the breakup of the relationship are situations that will influence the relational dynamics of a couple and may cause violent behavior to appear, increasing such behavior if it already existed or even giving rise to mortal violence. This paper analyzes the temporal distances between (1) the first complaint, (2) the last complaint, (3) the most recent complaint, and (4) the breakup with femicide. Two subsamples were used, one with 40 femicides with a prior complaint and another with 76 femicides with breakup. The analyzes showed that the time between complaints and femicide is very lengthy. The level of risk of the victims, as well as the control and violent behaviors, influence whether more or less time passes. On the other hand, there seems to be a connection between breakup and femicide since, in more than half of the cases, less than three months pass until the femicide, also influencing the existence of control and violent behaviors.